(untitled) (Journal of Economic Research & Business Administration, 2018)
The problems of entrepreneurial universities formation in the Republic of Kazakhstan are considered in this article, the analysis of the theoretical and methodological base of the research subject is presented, and the current state of Kazakhstan practice is described. The purpose of the work is to consider the real difficulties of transforming Kazakh universities into entrepreneurial ones and to offer solutions for these problems on the basis of a detailed analysis of the progressive practice of creating entrepreneurial universities. The methodological basis of the work is made up of such general economic methods as the method of dialectical and historical materialism, the method of induction and deduction, methods of statistical analysis, namely the collection and grouping of statistical data. The results of the study allowed the authors to conclude that the implemented model of the entrepreneurial university should take into account the institutional features of the country and the possibilities of the university. At the same time, an important component of their successful activity is the availability of highly qualified managers and teachers who have an entrepreneurial vision and idea, creative thinking, the pursuit of success, a willingness to take risks without fear of changes. The scientific and practical value of the work is that the recommendations contained in it will allow improving management approaches in the creation of entrepreneurial universities. Therefore, they will make it possible to take a serious step in the development of the domestic market for science-intensive products and the provision of resources for higher education, and will contribute to the modernization of the entire Kazakh economy.